PENGARUH FAKTOR-FAKTOR FUNGSIONAL, PSIKOLOGI DAN KONTEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK E-COMMERCE WEBSITE GROUPON - Indria Kesuma Hastuti (MIX: JURNAL ILMIAH MANAJEMEN, 2013)
Abstract: This study aimsto identify and analyzethe influence offunctionalfactors, psychology, andcontenton product purchasing decisionsone-commerce websitegroupon. The independent variablein this study isthe functionalfactors, psychological factors, andthe factor content, product purchasing decisions whilee-commerce is the dependent variable. In this study, data were collected by questioner.This questioner were distributed to respondents who had made a purchaseof goods or services throught he website groupon. The Sample used purposive sampling metho. Where as for filling out the questionnaire tobe taken with accidental sampling. Fromthe result of data processing the functional factor variables affected to the purchase decisione-commerce productson the group on website, variable factor spsycholog not affected to purchase decision e-commerce productson the group on website and factor content factor affected topurchasedecision e-commerceproductson thegrouponwebsite. The conclusion of this study, to increase consumer purchases the company must make improvements to increase the quality ofthe web site functionality, usabilility and content so that consumers feel comfortable and safty buying in the group on website.Keywords: usability, interactivity, online trust, aestheticsweb, marketing mix, ecommerce.